Learning Tools for Artificial Intelligence Implementation - Herlawati, Herlawati (LPPM Universitas Islam 45 Bekasi, 2024)
According to the rules of the Indonesian National Qualifications Framework (KKNI), undergraduate students fall into levels 5 and 6. Here, graduates are required to have the ability to apply existing knowledge according to the needs of the job. However, laboratory facilities that provide such competencies are very difficult to provide, especially for private campuses that rely on funding from students. This research tries to anticipate the gap between students' abilities and industry demands by providing laboratory facilities that do not require large costs. One of the courses demanded for students to master is Artificial Intelligence (AI), which has now spread to various fields. However, the curriculum currently applied usually focuses only on methods commonly used in the field of AI, while implementation in corporate fields requires direct application in the form of applications. Research results prove that several online applications can be used as substitutes for laboratories, including Google Colab, Play with Docker, Streamlit, and Teachable Machine. Compared to providing servers, computers containing development applications, using computers or laptops connected to the internet, students can easily implement the AI knowledge they have learned. For group work, applications for Continuous Integration/Continuous Delivery can be utilized, for example with Github, Gitlab, and similar ones.